Paisajes de la campaña pampeana (siglos XIX y XX) : abordajes desde la Arqueología rural en Argentina - Landa, Carlos,; Pineau, Virginia,; Montarani, Emanuel,; Doval, Jimena, (South American archaeology series ;, 2018)
This volume presents a series of papers designed to offer a summary of ongoing research across Argentina that can come under the broad heading of Rural Archaeology.